Author Correction: Assessing the Dynamics and Control of Droplet- and Aerosol-Transmitted Influenza Using an Indoor Positioning System - Timo Smieszek (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.